(untitled) (Elmergib Journal of Human Sciences, 2026)
This study aims to analyze the impact of integrating philosophy into graduate programs by reviewing prominent global experiences, identifying the main challenges and obstacles facing the integration process, and proposing practical mechanisms to implement it within universities. The study relied on the descriptive-analytical method, which allows for the analysis of educational and intellectual phenomena in light of real practices, through examining the theoretical framework of philosophy and its role in developing critical thinking, as well as analyzing applied experiences in some universities. The study concluded that integrating philosophy constitutes a fundamental axis in the development of graduate programs, due to its effect in enhancing students’ critical and value-based thinking and improving the quality of research outputs. However, Arab universities still face institutional, intellectual, and financial challenges that hinder this integration, necessitating the adoption of a comprehensive reform vision based on curriculum redesign, academic staff training, establishing research centers for philosophical thought.